Lacking Communication Would Increase General Symptom Index Scores of Medical Team Members During COVID-19 Pandemic in China: A Retrospective Cohort Study - Jinlong Zhang MD; Yunyun Fang MD; Zhaohui Lu MD; Xia Chen B.A; Na Hong PhD; Cheng Wang MD (SAGE Publishing, 2021)
There are few studies on the psychological status of medical staff during the COVID-19 outbreak. Our study addresses whether lack of communication affects the psychological status of medical team members supporting Wuhan during the COVID-19 pandemic in China. We used general symptom index (GSI) scores of the Symptom Checklist-90 (SCL-90) to evaluate participants' psychological status. We adopted a stratified sampling method and selected the fourth team, with a total of 137 members, as participants. In total 76.6% and 69.7% of female and male participants, respectively, had bachelor's degrees; 41.6% and 21.2% of female and male participants, respectively, were unmarried. Regarding communication, 14.29% and 6.06% of female and male participants, respectively, reported a lack of communication with the team (LCWT). Additionally, 13.0% and 6.1% of female and male participants, respectively, experienced fear of being infected (FoBI). LCWT and FoBI were positively correlated with GSI score (estimated change = 0.2, 95% CI [0.1-0.3]). When adjusted for gender, age, and FoBI, LCWT was positively correlated with GSI score ( P  < .05). Increasing communication among medical team members can reduce GSI scores.